Formulation and evaluation of physical stability and antidiabetic activity from nanoliposomes containing an ethyl acetate extract of Solanum xanthocarpum Schrader & Wendland fruit in rats - Yettrie Simarmata; Anayanti Arianto; Tri Widyawati; Pandapotan Nasution (Shahrekord University of Medical Sciences, 2024)
Introduction: The extract of Solanum xanthocarpum fruit has antidiabetic activity. This research aims to formulate nanoliposomes containing ethyl acetate extracts of S. xanthocarpum selected from multilevel extraction, evaluate their physical stability and antidiabetic activity, and compare them with the extract. Methods: The extracts were prepared using n-hexane, ethyl acetate, ethanol, and water as solvents, and their antidiabetic activities were evaluated to select the extract most effective in lowering blood sugar levels in rats. That extract was formulated into three nanoliposomes using varying amounts of phospholipid, cholesterol, and Span 60, i.e., F1 (40 mmol), F2 (50 mmol), and F3 (60 mmol). Various sonication times ranging from 10 to 30 minutes were evaluated for particle size, entrapment efficiency, and physical stability. The selected formulations were evaluated for antidiabetic activity. Results: The ethyl acetate extract showed the highest decrease in glucose in rats and was selected for nanoliposome formulation. The nanoliposomes obtained were physically stable at low temperatures for 12 weeks. F2 had the smallest particle size (143.97 nm) and the greatest entrapment efficiency (92.981% ± 0.35%) with a sonication time of 30 minutes and was significantly different from F1 and F3 (P<0.05). The highest percentage reduction in blood sugar levels was with F2 at 74.57% and significantly differed (P<0.05) from the ethyl acetate extract of S. xanthocarpum at 73.98% and the positive control rat group. Conclusion: The results show the potential uses of the prepared nanoparticles, especially the F2 formulation, as an antidiabetic formula.